Nauczanie i uczenie się języków obcych a otoczenie naukowe. Specyficzna harmonia nauk humanistycznych i społecznych w kształceniu nauczycieli języków obcych - Peć, Beata Anna (Neofilolog, 2025)
Can we really talk about the education of foreign language teachers? Or, more accurately, are we dealing with the process of shaping future teachers of English, German, Romance languages, Slavic languages, etc.? Which fields of research should be considered in this context? Which discipline leads the way: the humanities, or perhaps, in parallel, the social sciences? What are the core disciplines that provide the foundation for acquiring knowledge, developing skills, and shaping the attitudes of future foreign language teachers? What is the interplay between these fields, and where do their scientific boundaries lie? What constitutes the optimal environment for preparing trainees? Furthermore, in which language should this process of developing foreign language teachers take place? This article seeks to answer these and similar questions by integrating insights from disciplines such as linguistics, psychology, pedagogy, and (glotto)didactics, as well as many other disciplines. The goal of this text is to highlight the unique synergy of this specific scientific environment in the contemporary process of educating foreign language teachers, and to explore the processes of learning and teaching these languages. The article is divided into three sections: a theoretical and historical part, which includes an analysis of selected documents and texts; a contemporary part, which examines the current state through the lens of practical educational research; and a prognostic part, which outlines future research perspectives and formulates new hypotheses.